2020
DOI: 10.3758/s13423-020-01824-6
|View full text |Cite
|
Sign up to set email alerts
|

Training-induced improvement in working memory tasks results from switching to efficient strategies

Abstract: It is debated whether training with a working memory (WM) task, particularly n-back, can improve general WM and reasoning skills. Most training studies found substantial improvement in the trained task, with little to no transfer to untrained tasks. We hypothesized that training does not increase WM capacity, but instead provides opportunities to develop an efficient task-specific strategy. We derived a strategy for the task that optimizes WM resources and taught it to participants. In two sessions, 14 partici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 57 publications
1
11
0
Order By: Relevance
“…In the nback case, it is the implicit understanding that rather than shifting item position in WM—the attended position in WM should be shifted—reducing the number of manipulations to 1 regardless of the formal load of n . As in the TRO task, not all participants show this huge improvement, but all those that do, discovered the efficient strategy ( Malinovitch et al. 2020 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the nback case, it is the implicit understanding that rather than shifting item position in WM—the attended position in WM should be shifted—reducing the number of manipulations to 1 regardless of the formal load of n . As in the TRO task, not all participants show this huge improvement, but all those that do, discovered the efficient strategy ( Malinovitch et al. 2020 ).…”
Section: Discussionmentioning
confidence: 95%
“…It would be interesting to see in the future the extent to which the TRO task is representative of other WM tasks in this aspect. We believe that reducing WM demands is a necessary part of forming efficient task-specific strategies for WM training tasks even though it can be only a part of it (see, e.g., Malinovitch et al. 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors argued that task‐specific working memory training improvement can only enhance performance on tasks with a similar structure where the same strategies can be successfully employed. Such strategy mediation effects have been more directly examined and observed in adults, where strategy instruction on working memory tasks significantly improved performance on the same and similarly structured working memory tasks compared to working memory training without strategies instruction (Forsberg et al, 2020; Malinovitch, Jakoby, & Ahissar, 2021). These findings, taken together, suggest that the transfer of working memory training to structurally similar non‐trained tasks may be due in part to the use of the same strategy in both training and non‐trained tasks and to the efficiency of such strategy use in working memory‐demanding conditions (e.g., Bailey, Dunlosky, & Kane, 2008; Fellman et al, 2020; von Bastian & Oberauer, 2013).…”
Section: Domain‐specific Approach Of Working Memory Trainingmentioning
confidence: 99%
“…Strategy use is an important aspect of memory and learning that contributes to individual differences in performance [1,2]. Earlier studies have indicated that spontaneous strategy employment is associated with higher performance in different memory tasks [3][4][5][6][7][8][9][10][11][12]. However, the within-task dynamics of memory strategy use remain largely unexplored.…”
Section: Introductionmentioning
confidence: 99%